2020
DOI: 10.1007/s11845-020-02264-w
|View full text |Cite
|
Sign up to set email alerts
|

Cellular immunotherapies for cancer

Abstract: Cancer is a major burden on the healthcare system, and new therapies are needed. Recently, the development of immunotherapies, which aim to boost or use the immune system, or its constituents, as a tool to fight malignant cells, has provided a major new tool in the arsenal of clinicians and has revolutionized the treatment of many cancers. Cellular immunotherapies are based on the administration of living cells to patients and have developed hugely, especially since 2010 when Sipuleucel-T (Provenge), a DC vacc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
42
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(47 citation statements)
references
References 129 publications
(169 reference statements)
0
42
0
Order By: Relevance
“…Autoimmune diseases with well-known target antigens, such as AQP4+ NMOSD and MOGAD, are good candidate diseases to investigate tolerance-inducing cell-based therapies, especially in an antigen-specific way. While next-generation cell-based therapies have entered the arena of cancer treatment [ 103 ], they are still in their infancy in the field of autoimmune diseases. Several challenges need to be solved to drive the field of tolerance-inducing cell-based therapies in NMOSD and MOGAD forward.…”
Section: Discussionmentioning
confidence: 99%
“…Autoimmune diseases with well-known target antigens, such as AQP4+ NMOSD and MOGAD, are good candidate diseases to investigate tolerance-inducing cell-based therapies, especially in an antigen-specific way. While next-generation cell-based therapies have entered the arena of cancer treatment [ 103 ], they are still in their infancy in the field of autoimmune diseases. Several challenges need to be solved to drive the field of tolerance-inducing cell-based therapies in NMOSD and MOGAD forward.…”
Section: Discussionmentioning
confidence: 99%
“…Recruitment of immune cells, like DCs or T cells, is a crucial process for the initiation of inflammation, wound healing and hepatic fibrosis, as well 36 . As the principal antigen-presenting cells, DCs play a central role in adaptive and innate immunity, including capturing, processing and presenting antigenic material to T lymphocytes 37,38 . Meanwhile, it was reported that IDO1 was critically involved in inflammatory cells infiltration, including macrophages, DCs, T cells, etc.…”
Section: Discussionmentioning
confidence: 99%
“… MSC carriers enhance anti-tumor efficacy of oncolytic virotherapy. ( 1 ) MSCs loaded with OVs. ( 2 ) MSCs provide a replication locale for OVs to produce more virus particles.…”
Section: Figurementioning
confidence: 99%
“…With the development of targeted therapies and cellular immunotherapies, such as T cell-based, natural killer (NK) cell-based and dendritic cell (DC)-based immunotherapies, the therapeutic efficacy of cancer treatment has been greatly improved ( 1 ). However, the overall remission and survival rate of patients with certain tumors has not been fundamentally addressed.…”
Section: Introductionmentioning
confidence: 99%